HYPOCHOLESTEROLEMIA IN CLINICALLY SERIOUS CONDITIONS - REVIEW - Vyroubal, Pavel; Chiarla, Carlo; Giovannini, Ivo; Hyspler, Radek; Ticha, Alena; Hrnciarikova, Dana; Zadak, Zdenek (Biomedical papers, 2008)
BACKGROUND: Cholesterol is an essential component of cell membranes, precursor of steroids, biliary acids and other components of serious importance in live organism. Cholesterol synthesis is a complicated and energy-demanding process. Real daily need of cholesterol and mechanisms of decline cholesterol levels in critical ill are unknown. During stressful situations a significant hypocholesterolaemia may be found. Hypocholesterolemia has been known for a number of years to be a significant prognostic indicator of increased morbidity and mortality connected with a whole spectrum of pathological conditions. The aim of article is the elucidation of the role and importance of hypocholesterolaemia during the intensive care.METHODS AND RESULTS: We examined studies that are engaged in problems of hypocholesterolemia in critically ill. Very low levels of total as well as LDL cholesterol are most frequently found in serious polytrauma, after extensive surgery, in serious infections, in protracted hypovolemic shock. It is still not clear whether hypocholesterolemia reflects only a serious metabolic disorder, which results from a life-threatening condition, or whether it has an active role in evolution and outcome.CONCLUSIONS: Hypocholesterolemia is commonly observed in critically ill patients. Nevertheless, it is not known whether it is a secondary manifestation of disease, or whether it actively contributes to deterioration of the disease. Although the contribution of hypocholesterolemia to mortality is modest compared with known risk factors such as increased severity of illness and the development of nosocomial infection, low serum lipid concentrations represent a potential therapeutic target in sepsis.
Keywords: Cholesterol/Hypocholesterolemia/Hypolipoproteinemia/SIRS/Cytokines/Polytrauma/ Sepsis/Critically ill